2015
DOI: 10.5897/err2015.2212
|View full text |Cite
|
Sign up to set email alerts
|

Influences of moral, emotional and adversity quotient on good citizenship of Rajabhat Universitys Students in the Northeast of Thailand

Abstract: The objective of this study is to investigate the influences of moral, emotional and adversity quotient on good citizenship of Rajabhat University's students in Northeastern Region of Thailand. The samples included 1,087 undergraduate students from 8 different Rajabhat universities. Data analysis was conducted in descriptive statistics and structural equation model. The results revealed that the adversity quotient and moral quotient had a positive direct effect on good citizenship with the significance level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…For example, teachers with a high level of control in facing problems and challenges in school will tend to have strong conscientiousness, sportsmanship, courtesy, and civic virtue. These findings align in line with the research results [18], [19] that AQ affects OCB. In addition, teachers with fluent interpersonal communication manifested in openness, empathy, supportiveness, positiveness, and equality [26] also tend to have adequate altruism, conscientiousness, sportsmanship, courtesy, and civic virtue [9].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For example, teachers with a high level of control in facing problems and challenges in school will tend to have strong conscientiousness, sportsmanship, courtesy, and civic virtue. These findings align in line with the research results [18], [19] that AQ affects OCB. In addition, teachers with fluent interpersonal communication manifested in openness, empathy, supportiveness, positiveness, and equality [26] also tend to have adequate altruism, conscientiousness, sportsmanship, courtesy, and civic virtue [9].…”
Section: Discussionsupporting
confidence: 93%
“…The dimensions of AQ if in a high-level condition can stimulate increasing teachers' OCB manifested in altruism, conscientiousness, sportsmanship, courtesy, and civic virtue [9]. Previous studies [18], [19] also indicated that AQ affects OCB. Based on studies, the first hypothesis in this study is: AQ has a direct effect on teachers' OCB (H1).…”
Section: Introductionmentioning
confidence: 95%
“…Various components can also access this information openly and the information provided is easy to understand. This will have an impact on broad information to the community and make the community care about the environment (Choudri et al, 2017;Istiana & Awaludin, 2018;Ito & Kawazoe, 2015;Norman, Nordin, Din, & Ally, 2016;Nurwidodo, Hendayana, Hindun, & Sarimanah, 2018;Paço & Rodrigues, 2016;Siphai, 2015;Yedla & Park, 2017).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In the same manner, a study conducted by Sunan (2015) on the influences of moral, emotional and adversity quotient on good citizenship stressed out that adversity quotient and moral quotient has a positive direct effect on good relationship based on the 0.01 level of significance, while emotional quotient has a negative direct effect on good citizenship with the significance level of 0.05.…”
Section: Adversity Quotientmentioning
confidence: 83%